Factors Affecting Terahertz Emission from InGaN Quantum Wells under Ultrafast Excitation - Saleem, Muhammad Farooq; Ashraf, Ghulam Abbas; Iqbal, Muhammad Faisal; Khan, Rashid; Javid, Muhammad; Wang, Tianwu (International Journal of Optics, 2023)
InGaN quantum wells (QWs) grown on c-plane sapphire substrate experience strain due to the lattice mismatch. The strain generates a strong piezoelectric field in QWs that contributes to THz emission under ultrafast excitation. Physical parameters such as QW width, period number, and Indium concentration can affect the strength of the piezoelectric field and result in THz emission. Experimental parameters such as pump fluence, laser energy, excitation power, pump polarization angle, and incident angle can be tuned to further optimize the THz emission. This review summarizes the effects of physical and experimental parameters of THz emission on InGaN QWs. Comparison and relationship between photoluminescence properties and THz emission in QWs are given, which further explains the origin of THz emission in InGaN QWs.